2010
DOI: 10.1002/micr.20792
|View full text |Cite
|
Sign up to set email alerts
|

Shaping the breast in secondary microsurgical breast reconstruction: Single‐ vs. two‐esthetic unit reconstruction

Abstract: The esthetic outcome is dictated essentially not only by the position, size, and shape of the reconstructed breast, but also by the extra scaring involved. In the present study, we conducted a visual analog scale survey to compare the esthetic outcome in delayed autologous breast reconstruction following two different abdominal flaps inset. Twenty-five patients had their reconstruction using the Single-esthetic Unit principle and were compared with 25 patients that their breast was reconstructed using the Two-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
24
0

Year Published

2012
2012
2017
2017

Publication Types

Select...
4
2

Relationship

1
5

Authors

Journals

citations
Cited by 11 publications
(24 citation statements)
references
References 16 publications
0
24
0
Order By: Relevance
“…A minimum of 6 months elapsed between the completion of radiation and reconstruction. All patients received a DIEP flap that was inset, following the single esthetic unit principle . In all cases, the internal mammary vessels were the recipient vessels.…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…A minimum of 6 months elapsed between the completion of radiation and reconstruction. All patients received a DIEP flap that was inset, following the single esthetic unit principle . In all cases, the internal mammary vessels were the recipient vessels.…”
Section: Methodsmentioning
confidence: 99%
“…These advantages include an inconspicuous flap reconstruction, a consistently better position of the inframammary fold and, a more natural transition from native and reconstructed tissues. Most importantly, we have shown that the single‐esthetic unit breast reconstruction is associated with higher patient satisfaction …”
mentioning
confidence: 92%
See 1 more Smart Citation
“…Initially, devised for planning nasal and facial reconstructive surgeries (56)(57)(58)(59), aesthetic subunit principle has also demonstrated to improve the cosmetic outcome and patient satisfaction when applied in autologous breast reconstructions (16)(17)(18). Recently, in a direct comparison study, Gravvanis et al have reported that insetting DIEP flaps as a single aesthetic subunit, where the inferior mastectomy skin flap is deepithelialized and overlaid by the free flap so that a new IMF is defined using the edge of the free flap, yields a more natural shape and a satisfactory scar pattern than flap insetting as a double subunit, where the IMF is preserved (19). Similarly, when the mastectomy skin envelope is compromised due to radiation or is lacking in volume due to the reconstruction being delayed, this can be overcome by insetting the DIEP flap in "dual-plane", below and above the pectoral muscle in the upper and lower pole respectively (20).…”
Section: Discussionmentioning
confidence: 99%
“…To this effect, Blondeel et al have outlined a "three-step" approach that can be applied systematically when shaping and insetting a DIEP flap in any clinical case: prepare the breast footprint, shape the conus, and cover the flap with appropriate skin envelope (14). Since then, a number of studies have published methods to improve the preparation of breast footprint and safe, reliable skin envelope by incorporating the breast aesthetic subunit principle and the "dual-plane" insetting techniques (15)(16)(17)(18)(19)(20). In contrast, it is challenging to report in writing how a surgeon transforms a 2D flap into a 3D structure and only a small number of authors have described their technique of shaping the breast conus (14,(21)(22)(23).…”
Section: Introductionmentioning
confidence: 99%